Identity of Fusarium species associated with collar rot and wilt in passion fruit (Passiflora edulis ) - Nassimbwa, Florence; Matovu, Enock; Kiggundu, Andrew; Charles, Changa; Godfrey, Sseremba; Francis, Mumbanza; John, Adriko (Student's Journal of Health Research Africa, 2022)
Despite the immense contribution of passion fruits to people’s livelihood on a global scale, the crop’s productivity remains low owing to fungal diseases causing up to 100% loss. Fungi are highly variable and the identity of species or variates responsible for recently devastating passion fruit wilt and collar rot diseases had not been characterized. This study was aimed at identifying pathogens causing wilt and collar rot symptoms in passion fruits. Fungi were isolated from diseased samples collected from three locations in Central Uganda to identify Fusarium spp associated with collar rot and wilting of passion fruit. This was established by differentiating mycelium pigmentation on Potato Dextrose Agar (PDA), examining slides at X40 magnification under a light microscope for specific macro and microconidia, and amplification with specific Transcription Elongation Factor-1α, TEF 1α primers for identification of Fusarium spp. It was revealed that wilting was associated with a single species, out of 6 selected isolates from the suspected wilted plant, 3 were Fusarium spp associated with the disease in the field but only one of these isolates was proved to be a pathogenic type Fusarium oxysporium. Collar rot was associated with one pathogenic Fusarium spp out of the 6 selected isolates. The results indicate that collar rot and Fusarium wilt are each caused by specific strains of Fusarium pathogens.